OPTIMUM CONDITIONS OF USING URINE ON FRESH WEIGHT OF CHINESE KALE - Sreela-or, Chakkrit (Life Sciences and Environment Journal, 2017)
Factors affecting on Chinese Kale fresh weight by urine were optimized using response surface methodology with central composite design. Investigated parameters included urine concentration, volume of urine and application rate frequency. Results revealed that the optimum conditions were a urine concentration of 25.04%, volume of urine of 76.09 ml/plant and application rate frequency of 6.00 day. Under the optimal conditions, a maximum fresh weight of 115.74 g was obtained. The confirmation experiment under optimal condition showed a fresh weight of 117.08 g. This was only 1.15%, different from the predicted values.